The Content Analysis of the Kompas Daily Headlines Concerning the Cases of Polri and KPK in the Period of October to December 2009 - Dwi Purnama Puspita Sari (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2010)
The results of this study indicate that the SKH Kompas tends to portray the way Police and the Commission reviews the problems using the political dimension and the dimension combinations. Topics canopies tend to review SKH Kompas legal process, provided information and the combi- nation is more dominant on the use of canopies in SKH Kompas, techniques tend to be dominated by discussion of editorial excerpts, but also combine with technical explanations, examples, statis- tics, and combinations. While for the type of editorials, many use a type of giving of information and types of combinations. It shows that the SKH Kompas more comprehensive media in conveying the editorial policies of the problems police and KPK.